2007
DOI: 10.1523/jneurosci.4822-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Action Representation of Sound: Audiomotor Recognition Network While Listening to Newly Acquired Actions

Abstract: The discovery of audiovisual mirror neurons in monkeys gave rise to the hypothesis that premotor areas are inherently involved not only when observing actions but also when listening to action-related sound. However, the whole-brain functional formation underlying such "action-listening" is not fully understood. In addition, previous studies in humans have focused mostly on relatively simple and overexperienced everyday actions, such as hand clapping or door knocking. Here we used functional magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
438
2
15

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(509 citation statements)
references
References 70 publications
38
438
2
15
Order By: Relevance
“…Through practice, it is hypothesised that the processing of task-relevant kinematic patterns (observed, heard, and/or performed) of the action is enriched and consolidated (Gallese, 2000). In keeping with the supramodal brain theory, the kinematic pattern created by the action resonates in the perceiver's own motor system whether the sound is seen or heard (Aglioti & Pazzaglia, 2010Cesari et al, 2014;Kohler et al, 2002;Lahav et al, 2007;Pizzamiglio et al, 2005;Rizzolatti & Craighero, 2004). Although this account is consistent with our findings, the actual neural processes supporting pick-up and use of information about another person's action through sound is in need of further investigation.…”
Section: Action Anticipation Through Its Sound Alone 23 23supporting
confidence: 87%
“…Through practice, it is hypothesised that the processing of task-relevant kinematic patterns (observed, heard, and/or performed) of the action is enriched and consolidated (Gallese, 2000). In keeping with the supramodal brain theory, the kinematic pattern created by the action resonates in the perceiver's own motor system whether the sound is seen or heard (Aglioti & Pazzaglia, 2010Cesari et al, 2014;Kohler et al, 2002;Lahav et al, 2007;Pizzamiglio et al, 2005;Rizzolatti & Craighero, 2004). Although this account is consistent with our findings, the actual neural processes supporting pick-up and use of information about another person's action through sound is in need of further investigation.…”
Section: Action Anticipation Through Its Sound Alone 23 23supporting
confidence: 87%
“…Music is ubiquitous, a human feature, as ancient as homo sapiens, deeply rooted in our biology, with a seemingly distinct and extensive functional neuroarchitecture, capable of inducing vivid, intense emotions, all of which makes it an appealing phenomenon to study different areas of human nature. Sensory-motor mechanisms can be also studied using music since they activate not only when performing, but also when listening to it (Lahav, Saltzman, & Schlaug, 2007;Zatorre, Chen, & Penhune, 2007;Haueisen & Knösche, 2001). …”
Section: Cognitive Neuroscience Of Musicmentioning
confidence: 99%
“…Calvo-Merino et al, 2005;Lahav et al, 2007). If the development of imitation, and the mirror neuron system, is instead experience-dependent, then it may draw on three kinds of experience: unimodal sensory (Ferrari et al, 2005), unimodal motor (Calvo-Merino et al, 2006) or sensorimotor experience (Heyes, 2001;Heyes et al, 2005;Keysers and Perrett, 2004;Lahav et al, 2007;Obayashi et al, 2001).…”
Section: Mapping Observed To Executed Actionsmentioning
confidence: 99%
“…Järveläinen et al (2004) found that the degree of primary motor cortex activation when observing actions involving chopsticks correlated with the amount of recent experience with using chopsticks. Furthermore, highly familiar actions activate human premotor cortex more than non-familiar actions (Grezes et al, 1998), and in musically naïve observers activation in mirror areas is elicited by the observation of guitar playing which they are required to imitate (Buccino et al, 2004;Vogt et al, 2007), and by hearing sequences of tones which they had learned to play on the piano (Lahav et al, 2007).…”
Section: Effects Of Learning and Expertise On The Mirror Neuron Systemmentioning
confidence: 99%